EXPLORING INTERDISCIPLINARY OF ENTREPRENEURSHIP RESEARCH FOCUSING ON FAILURES AND SUCCESSES OF ENTREPRENEURS: - Silweya, Timothy (Universitas Nusa Cendana, 2025)
This paper aimed to explore the interdisciplinary nature of entrepreneurship research focusing on the failures and successes of entrepreneurs. A sample of 15 journal articles was purposively selected from 28 papers searched on Google Scholar. The inclusion and exclusion criteria were based on whether the paper’s main focus was entrepreneurial success or failure. Data were organized by theme: research design, academic discipline, and practices. The finding shows the majority of entrepreneurial studies (80%) employ qualitative design. 20% of these studies focused on theory building, 38% of failure factors were attributed to environmental forces (praxis), and 42% to practices. 62% of success factors were associated with practices and 58% with environmental forces. Researchers and scholars in the entrepreneurship field and practitioners will find this paper useful. Further research is recommended to explore entrepreneurship training and education offered in learning institutions. Keywords: Entreprenology, Entrepreneurship Education; Entrepreneurship Praxis and Practice